PARylation prevents the proteasomal degradation of topoisomerase I DNA-protein crosslinks and induces their deubiquitylation - Yilun Sun (Nature Portfolio, 2021)
TOP1 resolves DNA supercoils by forming cleavage complexes (TOP1cc) that are trapped by TOP1 inhibitors. Here the authors provide insights into the mechanistic understanding of TOP1cc PARylation, showing that inhibition of PARG results in stabilization of TOP1cc PARylation that blocks the proteasomal degradation of TOP1cc.